2018
DOI: 10.3390/ijerph15112582
|View full text |Cite
|
Sign up to set email alerts
|

Water Sustainability at the River Grande Basin, Brazil: An Approach Based on the Barometer of Sustainability

Abstract: Water resources are fundamental for the social and economic development of a country and sustainability is the best approach to treat water-related problems. Therefore, sustainability studies of water resources are deemed urgent. Sustainability analysis methods should enable space-temporal monitoring, decision-making, and development of policies necessary for water governance. Furthermore, sustainability analysis methods should also integrate environment and socioeconomic variables into a single system. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, it is important to highlight that socioeconomic development must be linked to environmental quality. This requires integrating water resources management with other public administration sectors that also affect water quality and availability [21]. Land management, closely related to land use and occupation, must be adapted in accordance to environmental, social and development policies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to highlight that socioeconomic development must be linked to environmental quality. This requires integrating water resources management with other public administration sectors that also affect water quality and availability [21]. Land management, closely related to land use and occupation, must be adapted in accordance to environmental, social and development policies.…”
Section: Resultsmentioning
confidence: 99%
“…BHRG is located in the southeastern region of Brazil and has a contribution area of approximately 145,000 km 2 divided between the state of Minas Gerais (60% of the total area of the basin) and the state of São Paulo (40% of the total area of the basin) (Figure 1) [21,22]. The basin is made up of 393 municipalities, totally or partially inserted in it, which corresponded to 4.5% of the Brazilian population in 2010.…”
Section: Study Areamentioning
confidence: 99%
“…The performance scale of the sustainability indexes is established subjectively in the water sustainability indexes (Guidolini et al, 2018), thus in this work is proposed a technique based on the coding of the subindexes ranking to improve the interpretation of the WMSI. Since the WMSI does not reflect the specific conditions of the sub-systems of the sub-basins, a combination matrix with the ESEI codes (Economic, Social, Environmental, and Institutional) was designed in which the scores of the sub-indexes were represented by codes.…”
Section: Weighting and Aggregation Of The Subindexesmentioning
confidence: 99%
“…The results indicated that the region is potentially unsustainable [30]. This method has been used in other studies to assess water sustainability and agricultural sustainability [31][32][33]. This assessment tool was chosen for measuring sustainability in the present study since it has some significant advantages over other approaches:…”
Section: Introductionmentioning
confidence: 99%